Claim Mechanism Analysis of Cash in Safe Products in the Completion of the Agreement between the Bank of Sumut and PT. Bumida Insurance 1967 - Azizah Rahmah; Tri Inda Fadhila Rahma (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractMoney insurance is an insurance that can provide protection against losses that will befall bank cash. The purpose of this study is to provide clear information about the claim mechanism in the settlement of the agreement between Bank Sumut and PT Asuransi Bumida 1967 Medan on cash in safe products. The research method uses qualitative methods with data collection techniques through interviews and literature studies. The results of this study show that the claim mechanism in the settlement of the agreement is that the company makes claim payments based on the submission of claim payments, namely the insured party submits official documents that will be followed up no later than 14 days after the claim payment submission documents are received by the insurer in good and sufficient condition.Keywords: Mekanisme Klaim, Perjanjian, Bank Sumut, Pt. Asuransi Bumida, Produk Cash In Safe